Geographical and seasonal variability in the development of aphids (Homoptera, Aphidinea) - A. K. Khusanov; M. Sh. Juraev; Z. S. Abdukadirova (Российский паразитологический журнал, 2022)
The purpose of the research is to study geographical and seasonal variability of aphids from the Ferghana Range.Materials and methods. The research materials were long-term collections, observations and experiments conducted in various zones of the Ferghana Range (Uzbekistan, Kyrgyzstan) in 2006–2020. The studies used entomological, aphidological and statistical methods. The V. Barov’s psi-square and Student and Fisher’s Z methods were used to compare the samples. Mathematical analysis was performed based on 16 morphometric characteristics from the samples of adult aphids (n = 10).Results and discussion. The morphological features of aphids during divergence are a key factor in their range forage and adaptation to it. Other environmental factors have undoubtedly a direct effect on aphids through forage plants in some cases. The study of morphometric parameters of the samples taken in Mayli-Say and Khanabad showed that the variability of the aphid’s hindleg was zero, and the samples from Mayli-Say differed significantly from the samples from Khanabad (P > 0.01). The study results confirm that the samples from both regions are mainly subject to geographical variability influenced by climatic and other factors, and the confidence level differs in morphometric parameters.